Incidence of and Risk Factors for Paradoxical Psoriasis or Psoriasiform Lesions in Inflammatory Bowel Disease Patients Receiving Anti-TNF Therapy: Systematic Review With Meta-Analysis - Xie, Wenhui; Xiao, Shiyu; Huang, Hong; Zhang, Zhuoli (Frontiers in Immunology, 2022)
Background Paradoxical psoriasis or psoriasiform lesions induced by anti-tumor necrosis factor (anti-TNF) therapies receive increasing attention worldwide. However, no comprehensive meta-analysis investigating the incidence estimates and risk factors for anti-TNF-induced psoriasis is currently available. We aimed to precisely quantify its incidence as well as risk factors in patients with inflammatory bowel disease (IBD). Methods This study was registered on PROSPERO database under review registration number CRD42021233695. The electronic databases PubMed, EMBASE, and the Cochrane library were comprehensively searched for observational studies published as full-length papers in English and reporting the incidence and/or predictors for psoriasis or psoriasiform lesions in IBD patients. A random-effects meta-analysis was performed to calculate the pooled incidence. Pooled odds ratio (OR) and 95% confidence interval for potential predictors were combined using a fixed-effects or random-effects model. Results In total, 30 articles comprising 24,547 IBD patients treated by anti-TNF were finally included. The overall pooled incidence of psoriasis and/or psoriasiform lesions following anti-TNF therapy was 6.0% (5.0–7.0%; I2 = 93.9%), with 6.9% (5.1–8.7%; I2 = 92.4%) for psoriasiform lesions and 4.6% (3.6–5.6%; I2 = 93.9%) for psoriasis. Multivariable meta-regression analysis indicated regions and populations that significantly contributed to the heterogeneity. A statistically higher risk for psoriasis or psoriasiform lesions during anti-TNF therapy was observed in female patients (OR 1.46, 1.23–1.73), those who are at a younger age at anti-TNF initiation (OR 1.03, 1.00–1.05), smokers (OR 1.97, 1.56–2.48), ileocolonic Crohn’s disease patients (OR 1.48, 1.03–2.13), and those who are using adalimumab or certolizumab (vs. infliximab) (OR: 1.48 and 2.87 respectively). Conclusions The incidence of psoriasis or psoriasiform lesions was not uncommon in IBD patients following anti-TNF therapy. Female, younger age, smoker, ileocolonic Crohn’s disease, and the types of anti-TNF were significantly associated with such risk. These findings may help gastroenterologists to make more individualized decisions and understand the mechanisms of this paradoxical phenomenon. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=233695, identifier CRD42021233695.